Psychological loneliness and its relationship to the trend towards forming virtual families among a sample of adolescents who use social networking - Alturkistani, Musab Amrullah (Journal of Educational and Psychological Sciences, 2022)
The research aims to reveal psychological loneliness and its relationship to the trend towards forming virtual families, The researcher used the descriptive method, and the research sample is (433) adolescents in the middle stage, their ages ranged from (15-18) years and social media users. The researcher has used the (UCLA) Loneliness Scale, translator by Magdy Dosouky (1998) to measure the level of Loneliness, and Alanezi & Suleiman (2019) scale to reveal the trend towards forming virtual families. The results indicated the adolescent sample suffers from an above-average level in terms of psychological loneliness, And they have a below-average range for the trend towards forming virtual families, And There is a negative correlation (a ≥ 0.001) between the feeling of loneliness and the tendency towards forming virtual families for them, and There are no differences between the average scores of adolescents on the loneliness scale depending on the variable number of strangers friends, and There are differences between the average scores of adolescents on the loneliness scale, depending on the variable number of hours of using social media, for the less frequently used adolescents. Finally, the study presented several recommendations and suggestions for further research.